Study of Linear Shrinkage for Siliceous Materials to Meet Insulating Requirements - A, Kamis R. (Iraqi Journal of Physics, 2011)
Iraqi siliceous rocks were chosen to be used as raw materials in this study which is concern with the linear shrinkage and their related parameters. They are porcelinite from Safra area (western desert) and Kaolin Duekla, their powders were mixed in certain percentage, to shape compacts and sintered. The study followed with thermal and chemical treatments, which are calcination and acid washing. The effects on final compact properties such as linear shrinkage were studied. Linear shrinkage was calculated for sintered compacts to study the effects of calcination processes, chemical washing, weight percentage, sintering processes, loading moment were studied on this property where the compacts for groups is insulating materials. Linear firing shrinkage test is very important in ceramic industries, when in some uses most be calculated the ceramic body volume before product. The results indicate that some of these groups satisfy ability the required linear firing shrinkage property for electrical insulator, so they are an ability to be used in industry